2013
DOI: 10.1177/1355819613505746
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for improving human resource outcomes in health care: overview of reviews

Abstract: Overall, evidence of effective strategies for improving outcomes is mixed. While financial incentives play a key role in enhancing outcomes, they need to be considered as only one strategy within an incentives package. There is stronger evidence that improving the work place environment and instituting mechanisms for work-life balance need to be part of an overall strategy to improve outcomes for health care practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 10 publications
1
24
0
2
Order By: Relevance
“…The incorporation of these support strategies into radiotherapy practice will likely promote RTs’ and ROMPs’ recruitment, job satisfaction and retention (Misfeldt et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The incorporation of these support strategies into radiotherapy practice will likely promote RTs’ and ROMPs’ recruitment, job satisfaction and retention (Misfeldt et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Based on the findings about aspects of work that were role enhancing and led to work satisfaction versus aspects that were not, Table 2 highlights recommendations which workplaces could adopt to support their RTs and ROMPs. The incorporation of these support strategies into radiotherapy practice will likely promote RTs' and ROMPs' recruitment, job satisfaction and retention (Misfeldt et al 2014). Radiation oncology medical physicists, in particular, reported that they did not feel valued in their role by the community, the multidisciplinary team and other parts of the organisation in which they worked.…”
Section: Discussionmentioning
confidence: 99%
“…It was also a surprising finding that otherwise well conducted reviews conflated evidence from self-reported determinants of turnover ( i.e. what reports groups of nurses say are the causes of their intent or action to leave) with the review authors’ opinions as to strategies to decrease turnover (including in a very recent overview [ 49 ]). While the reviews we overviewed make it clear that there remains much to be done to improve the strength of evidence, for example there are no controlled trials and very few attempts to control observational studies, we argue such misapplied conflation has restricted the development of true intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…(124) We updated the search and added one Evidence >> Insight >> Action overview of systematic reviews about the effects of pay-for-performance that was published since the evidence brief about financial incentives was completed. (135) The following are the key messages that were included in the evidence brief from 2015 about financial incentives for consumers, health professionals and organizations, which we have updated slightly using the newly identified overview: 1) financial incentives targeting citizens can be effective at changing behaviours such as those required before surgery (e.g., smoking cessation), but the evidence supporting these effects is either inconsistent (e.g., for improving adherence to medicines), (136) indicates that effects are not sustained in the long term (e.g., for promoting healthy behaviours such as changes in smoking, eating, alcohol consumption, and physical activity), (137)(138)(139) or require substantial cash incentives to sustain behaviour changes (e.g., for smoking cessation);(140) 2) the reviews of the evidence for the use of financial incentives for providers, (141)(142)(143)(144)(145) health organizations (146) and for both providers and health organizations, (135; 147-149) found that:…”
Section: Scale Up Successful Effortsmentioning
confidence: 99%